Efektivitas Model Discovery Learning dengan Media Wordwall terhadap Kemampuan Literasi Matematika dan Kemandirian Belajar Peserta Didik MTs NU Hasyim Asy’ari 2 Kudus - Shofia, Laila; Setiaji, Heru Agni (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
The ability to understand, apply, and interpret mathematical concepts in the context of real life is known as mathematical literacy. However, Indonesian mathematical literacy is still inadequate, as shown by the results of the 2022 PISA survey. The same thing happened at MTs NU Hasyim Asy'ari 2 Kudus. Based on the results of the preliminary test related to the aspect of mathematical literacy, the average score was 24.85 (25% passed the KKM). In addition, students' learning independence is less than optimal because learning is more teacher-centered. A more active and creative learning approach, such as discovery learning with wordwall media, is needed to overcome this problem. The purpose of this study was to examine the improvement of mathematical literacy and learning independence of students at MTs NU Hasyim Asy'ari 2 Kudus through the paradigm of the discovery learning model with wordwall media. This research method uses a quantitative approach with a quasi-experimental type. The sampling technique applied was cluster random sampling, where class VIII-A was the experimental class and class VIII-D was the control class. Data were collected through tests and questionnaires, then analyzed using independent sample t-test and N-Gain test after fulfilling the normality test and homogeneity test. The results showed that there was a significant difference in learning independence between the two classes, with a significance value (2-tailed) of 0.001 (<0.05). Meanwhile, the results of the N-Gain test of mathematical literacy skills showed an average value of the experimental class of 76.5% which was categorized as effective, while the average value of the control class was 32.1% which was categorized as ineffective. Thus, the integration of the discovery learning model with wordwall media can improve mathematical literacy and student learning independence at MTs NU Hasyim Asy'ari 2 Kudus